Momordica. charantia-Derived Extracellular Vesicles-Like Nanovesicles Protect Cardiomyocytes Against Radiation Injury via Attenuating DNA Damage and Mitochondria Dysfunction - Wen-Wen Cui (Frontiers in Cardiovascular Medicine, 2022)
Thoracic radiotherapy patients have higher risks of developing radiation-induced heart disease (RIHD). Ionizing radiation generates excessive reactive oxygens species (ROS) causing oxidative stress, while Momordica. charantia and its extract have antioxidant activity. Plant-derived extracellular vesicles (EVs) is emerging as novel therapeutic agent. Therefore, we explored the protective effects of Momordica. charantia-derived EVs-like nanovesicles (MCELNs) against RIHD. Using density gradient centrifugation, we successfully isolated MCELNs with similar shape, size, and markers as EVs. Confocal imaging revealed that rat cardiomyocytes H9C2 cells internalized PKH67 labeled MCELNs time-dependently. In vitro assay identified that MCELNs promoted cell proliferation, suppressed cell apoptosis, and alleviated the DNA damage in irradiated (16 Gy, X-ray) H9C2 cells. Moreover, elevated mitochondria ROS in irradiated H9C2 cells were scavenged by MCELNs, protecting mitochondria function with re-balanced mitochondria membrane potential. Furthermore, the phosphorylation of ROS-related proteins was recovered with increased ratios of p-AKT/AKT and p-ERK/ERK in MCELNs treated irradiated H9C2 cells. Last, intraperitoneal administration of MCELNs mitigated myocardial injury and fibrosis in a thoracic radiation mice model. Our data demonstrated the potential protective effects of MCELNs against RIHD. The MCELNs shed light on preventive regime development for radiation-related toxicity.